2021
DOI: 10.1016/j.ejrad.2021.109755
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of inflammatory from degenerative changes in the sacroiliac joints by machine learning supported texture analysis

Abstract: To compare the diagnostic performance of texture analysis (TA) against visual qualitative assessment in the differentiation of spondyloarthritis (SpA) from degenerative changes in the sacroiliac joints (SIJ). Method: Ninety patients referred for suspected inflammatory lower back pain from the rheumatology department were retrospectively included at our university hospital institution. MRI at 3 T of the lumbar spine and SIJ was performed with oblique coronal T1-weighted (w), fluid-sensitive fat-saturated (fs) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…Notably, our dataset displays a significantly higher count of negative cases compared to positive ones, a pattern also seen in the literature [16], as well as other radiomics studies [17]. This discrepancy led to concerns about potential biases during algorithm training.…”
Section: Segmentation and Feature Extractionsupporting
confidence: 57%
See 1 more Smart Citation
“…Notably, our dataset displays a significantly higher count of negative cases compared to positive ones, a pattern also seen in the literature [16], as well as other radiomics studies [17]. This discrepancy led to concerns about potential biases during algorithm training.…”
Section: Segmentation and Feature Extractionsupporting
confidence: 57%
“…Their study included a total of 90 patients. However, their most accurate outcomes were generated by a model that employed T1W-CE images [17]. This model which was built upon contrast-enhanced images demonstrated the highest accuracy, probably by detecting ancillary inflammatory lesions like synovitis or enthesitis, which could suggest inflammation [4].…”
Section: Discussionmentioning
confidence: 99%
“…In KEPP et al's study, texture analysis based on radiomics was superior to qualitative evaluation in distinguishing sacroiliac arthritis from degenerative changes. The diagnostic AUC of multiple imaging sequences combined by radiologists is 0.72, the AUC of fsT1wCE is 0.87, the AUC of T1w sequence is 0.49, and the AUC of the combined fsT1wCE multiple sequence combination is 0.91 [ 41 ]. As shown in Table 4 , in this study, the SVM-bimodal model with conventional MRI sequence achieved better AUC results in the testing set compared to KEPP et al's radiomics-based texture analysis model special MRI sequences, thus further improving the efficiency of assisting in the diagnosis of sacroiliitis and our model uses conventional MRI sequences, which have better clinical applicability.…”
Section: Discussionmentioning
confidence: 99%
“…So, there may be some false positives in practical diagnosis. Kepp et al (2021) indicated that two radiologists with a minimum of 5 years of experience only have an accuracy rate of 75.6% and 74.4% in the diagnosis of sacroiliitis, respectively. Furthermore, the networks generalization ability would decrease due to the distributional imbalance of sacroiliitis and especially the lack of grade IV samples.…”
Section: And Radiomics Methodsmentioning
confidence: 99%
“…Sacroiliitis is visually assessed on CT scans using gray scale descriptors, texture descriptors, which are effective prior features for mitigating the risk of over-fitting. As a result, radiomics has been applied extensively in the diagnosis of sacroiliitis (Faleiros 2018, Castro-Zunti et al 2020, Tenório et al 2020, Kepp et al 2021, Ye et al 2022. Ye et al (2022) improved the diagnostic accuracy from 74% to 78% using a model that combined the features of radiomics and clinical practice.…”
Section: And Radiomics Methodsmentioning
confidence: 99%